Edaravone protects endotoxin-induced liver injury by inhibiting apoptosis and reducing proinflammatory cytokines - Zong, L. (Associação Brasileira de Divulgação Científica, 2014)
Studies have shown that edaravone may prevent liver injury. This study aimed to investigate the effects of edaravone on the liver injury induced by D-galactosamine (GalN) and lipopolysaccharide (LPS) in female BALB/c mice. Edaravone was injected into mice 30 min before and 4 h after GalN/LPS injection. The survival rate was determined within the first 24 h. Animals were killed 8 h after GalN/LPS injection, and liver injury was biochemically and histologically assessed. Hepatocyte apoptosis was measured by TUNEL staining; proinflammatory cytokines [tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6)] in the liver were assayed by ELISA; expression of caspase-8 and caspase-3 proteins was detected by Western blot assay; and caspase-3 activity was also determined. Results showed that GalN/LPS induced marked elevations in serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT). Edaravone significantly inhibited elevation of serum AST and ALT, accompanied by an improvement in histological findings. Edaravone lowered the levels of TNF-α and IL-6 and reduced the number of TUNEL-positive cells. In addition, 24 h after edaravone treatment, caspase-3 activity and mortality were reduced. Edaravone may effectively ameliorate GalN/LPS-induced liver injury in mice by reducing proinflammatory cytokines and inhibiting apoptosis.